Sonochemical Assisted Synthesis of Cr-PTC Metal Organic Framework, ZnO, and Fe3O4 Composite and Their Photocatalytic Activity in Methylene Blue Degradation - Nurbayti, Siti; Adawiah, Adawiah; Bale, Uly Fitria; Fadhilla, Rizka; Ramadhan, Fitri Nur; Zulys, Agustino; Sukandar, Dede; Saridewi, Nanda; Tulhusna, Latifah (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
Methylene blue pollutants can be treated by photocatalytic methods using metal oxide-based semiconductor materials and metal organic framework (MOF). These two materials are often coupled into a composite to improve their physicochemical properties and catalytic activity. This research focuses on the synthesis of composites based on Cr-PTC MOF, ZnO, and Fe3O4 by the sonochemical method. The obtained composites were characterized and tested for catalytic activity in methylene blue pollutant degradation in an aqueous system under acidic conditions (pH = 5). Our investigation shows that the Cr-PTC@Fe3O4 composite possesses the lowest band gap energy of 1.86 eV and achieves the highest photocatalytic activity in methylene blue degradation at solution pH = 5, with a percent degradation of 84.36%. The sonochemical incorporation of Fe3O4 and Cr-PTC MOF is able to fabricate materials in a short time with better photocatalytic activity in degrading methylene blue than the single materials. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).